2022
DOI: 10.3389/fmolb.2021.821506
|View full text |Cite
|
Sign up to set email alerts
|

The Tissue Distribution of SARS-CoV-2 in Transgenic Mice With Inducible Ubiquitous Expression of hACE2

Abstract: The novel coronavirus disease COVID-19 has become one of the most socially significant infections. One of the main models for COVID-19 pathogenesis study and anti-COVID-19 drug development is laboratory animals sensitive to the virus. Herein, we report SARS-CoV-2 infection in novel transgenic mice conditionally expressing human ACE2 (hACE2), with a focus on viral distribution after intranasal inoculation. Transgenic mice carrying hACE2 under the floxed STOP cassette [(hACE2-LoxP(STOP)] were mated with two type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…5D). To confirm efficacy in a more severe model, we examined the effect of engineered ACE2 on survival of CAG–human ACE2 (hACE2) mice that overexpress hACE2 highly and ubiquitously and exhibit more severe SARS-CoV-2 transmission to the brain ( 13 ), as compared with K18-hACE2 mice directing epithelia-specific expression ( 14 16 ). The mice were challenged with 1 × 10 3 PFU of Omicron through the intranasal route, and engineered ACE2 was intravenously administered 2 hours after inoculation at a dose of 20 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…5D). To confirm efficacy in a more severe model, we examined the effect of engineered ACE2 on survival of CAG–human ACE2 (hACE2) mice that overexpress hACE2 highly and ubiquitously and exhibit more severe SARS-CoV-2 transmission to the brain ( 13 ), as compared with K18-hACE2 mice directing epithelia-specific expression ( 14 16 ). The mice were challenged with 1 × 10 3 PFU of Omicron through the intranasal route, and engineered ACE2 was intravenously administered 2 hours after inoculation at a dose of 20 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized that erythrocyte aggregates were present in the lung tissue in abundance, which was indicative of clotting. In contrast to lung tissue samples, no aberrations were found in the histologi cal examination of the brain except for abundant erythrocyte aggregates as a sign of clotting (Dolskiy et al, 2022). All experimental transgenic mice died on day 5 to 10 after the intranasal inoculation.…”
Section: Technologies For the Creation Of Transgenic Mice For Modelin...mentioning
confidence: 85%
“…In heterozygous ACE2-GFP and Cre-transgene mice, the transgene was ac tivated with tamoxifen, which activates Cre-UBC, which, in turn, cuts out the STOP cassette and activates the expression of ACE2 and the reporter gene (Bruter et al, 2021). Thus, heterozygous mice become susceptible to coronavirus infec tion (Dolskiy et al, 2022).…”
Section: Technologies For the Creation Of Transgenic Mice For Modelin...mentioning
confidence: 99%
“…Their results further suggested that severity and infection progress is dependent on the particular Cre driver, more specifically on its expression potency. Furthermore, relatively recent changes in renin-angiotensin system due to hACE2 overexpression can be another factor influencing response to the infection (Dolskiy et al, 2022).…”
Section: Hace2(loxp-stop) Modelmentioning
confidence: 99%
“…et al, 2007;Yang XH. et al, 2007;McCray et al, 2007;Tseng et al, 2007;Menachery et al, 2016;Jiang et al, 2020;) Bruter et al, 2021Dolskiy et al, 2022).…”
Section: Lenti-hace2mentioning
confidence: 99%